Low-temperature sintering behavior of fly ash from hazardous waste incinerator: Effect of temperature and oxygen on ash properties. Issue 3 (June 2021) - Yan, Mi; Zhou, Zhihao; Zheng, Rendong; Jiang, Jiahao; Feng, Hongyu; Yu, Caimeng; Zhu, Gaojun; Hantoko, Dwi
Abstract: Hazardous waste incineration fly ash (HFA) is high risk for the environment due to heavy metals leaching and other pollutants. Sintering treatment potentially reduces the mass and volume of HFA and immobilizes heavy metals in ceramic-like bodies. However, HFA contains a large amount of heavy metals, thus sintering at too high a temperature will lead to the volatilization of heavy metals. The low-temperature sintering behavior of HFA at different temperature (450 °C, 670 °C and 900 °C) and different atmospheres (21% O2, 47.3% O2, 60.5% O2 and 100% O2 ) was investigated in this study. The mass loss, morphology, bulk density, elemental composition, heavy metal leaching rate, and mineral phase transformation of sintered ash were experimentally tested. With increasing sintering temperature, more mass of HFA was lost and the leaching rate of heavy metals decreased. For instance, sintered at 450 °C, 670 °C and 900 °C under air, the mass losses were 4.30%, 6.58%, and 17.96%, the leaching rate of Pb were 19.37%, 2.74%, and 0.65%, respectively. Sintered ash became denser and formed ceramic-like particle due to thermal agglomeration and chemical reactions. The bulk density significantly increased, which was favorable to reduce space occupancy for fly ash landfill. Oxygen-rich atmosphere could make the fly ash denser and inhibit the volatilization and leaching of Pb. The obtained findings are beneficial for deep understanding of the sintering behavior of HFA at low-temperature. Graphical Abstract: ga1 Highlights: HFA was sintered under different atmospheres (21% O2 –100% O2 ) at 450–900 °C. The mass loss of HFA increased with increasing sintering temperature. The sintered ash became denser and formed a ceramic-like particle. The mineral phase transformations occurred between 450 °C and 670 °C. The leaching rate of heavy metals decreased after sintering.